KEBIJAKAN PERENCANAAN ANGKUTAN MASSAL DI KOTA BOGOR - Chrisgerson Rudor; Muhammad Findi Alexandi (IPB University, 2012)
Density and population of bogor that keeps increasing will add the duty of government to provide more public means of mass. Transportation is a vital public facility. Public transport available in Bogor is a city transportation (public transportation) and buses. The existence of a number of public transportation totaling 3,412 units and 30 units of bus has been able to serve the needs of the community in transportation, but in terms of efficiency and comfort are still far from expected. Based on the results of Stated Preference regression models, we concluded that the most efficient mass transportation is city buses, and the most variable priority attribute passengers on a city bus is the bus occupancy, the bus waiting time efficiency, got a seat, bus convenience and cost/ bus rates. So the recommendation that we can give, the problem due to public transport in bogor can be solved by the means of mass transportation such as city buses. Keywords: Density and population of Bogor, PublicTtransportation, Stated Preference Models